Cardiac amyloidosis secondary to waldenström macroglobulinemia - Lachira-Yparraguirre, Lizbeth (2020)
Introduction: Waldenström's macroglobulinemia is a hematological neoplasm belonging to the group of monoclonal gammopathies, which includes systemic symptoms and those related to an increase in M paraprotein. Objective: To describe a case of cardiac amyloidosis associated with macroglobulinemia. Clinical case: Male patient who was admitted for asthenia, dysphonia, and who, during his evolution, developed progressive dyspnea, heart failure and pleural effusion. Additionally, echocardiography showed myocardial granular pattern, while pleural biopsy was positive for Congo red staining. Subsequently, he received treatment with bortezomib, dexamethasone and rituximab, with favorable evolution. Conclusions: In this disease, early diagnosis is an important advantage for survival. Therefore, its management is palliative of cardiac manifestations. The present case shows a diagnostic challenge, in which the less frequent etiologies of heart failure must be taken into account.